2022
DOI: 10.1039/d2qi00995a
|View full text |Cite
|
Sign up to set email alerts
|

Towards large area surface functionalization with luminescent and magnetic lanthanoid complexes

Abstract: Homogeneous surface deposition of molecules over a large area of substrate is difficult to achieve but extremely important for proposed applications of magnetic molecules in data storage, information processing or...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…We followed the procedure modified from Godoy-Gallardo et al 26 reported by us. 27 Resultant layer thickness was measured with ellipsometry, the TSP layers were consistently between 1 and 1.5 nm. Hydrophobicity of the resultant surface was measured with a homemade contact angle meter (48°).…”
Section: Methodsmentioning
confidence: 99%
“…We followed the procedure modified from Godoy-Gallardo et al 26 reported by us. 27 Resultant layer thickness was measured with ellipsometry, the TSP layers were consistently between 1 and 1.5 nm. Hydrophobicity of the resultant surface was measured with a homemade contact angle meter (48°).…”
Section: Methodsmentioning
confidence: 99%
“…The intermediate layers are self-assembled monolayers (SAMs) of organic molecules, with ref. 34 or without 28 , 30 , 31 , 33 long tethered organic groups. These two cases complicate the use of ESR-STM.…”
Section: Molecular Properties On a Surfacementioning
confidence: 99%
“…It is now clear that substrate phonons and the electron cloud of metallic substrates can couple with the magnetic molecules and affect the nanomagnets properties: to solve this, intermediate or buffer layers have been used with success, for example in the case of [Tb(Pc) 2 ] SMM, (Pc = phthalocyanine ligand), from now on TbPc 29 What happens with other compounds, with more complex structures than the TbPc SMM? There are several examples that show that a buffer layer (that can be organic or inorganic in nature) can be used effectively to ensure a weak molecule-surface interaction 28 , 30 32 In fact, the organic buffer layer can also be used to graft the molecule on a substrate 33 35 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 To the best of our knowledge, there are only two studies of a Dy III complex immobilized on functionalized silicon wafers. 7,9 Most of these Ln III complexes grafted on silicon wafers [5][6][7]9 are obtained by immersion of the functionalized surface in a solution of the complex. However, this straightforward approach presents serious drawbacks regarding the achievement of compact deposition and therefore robust monolayers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, reports on Ln III compounds immobilized on this type of substrate are scarce and are mostly related to the surface luminescence studies of Eu III and Tb III complexes. In the case of Dy III compounds, most of the reports about deposition on solid surfaces are focused on magnetic studies, using as substrate gold , or silica particles. , To the best of our knowledge, there are only two studies of a Dy III complex immobilized on functionalized silicon wafers. , Most of these Ln III complexes grafted on silicon wafers , are obtained by immersion of the functionalized surface in a solution of the complex. However, this straightforward approach presents serious drawbacks regarding the achievement of compact deposition and therefore robust monolayers.…”
Section: Introductionmentioning
confidence: 99%